Supportive care of female hormones in brain health: what and how? - Zhu, Afang; Song, Shujia; Pei, Lijian; Huang, Yuguang (Frontiers in Pharmacology, 2024)
Female hormones, functioning as neuroactive steroids, are utilized beyond menopausal hormone therapy. The rapid onset of allopregnanolone analogs, such as brexanolone and zuranolone, in treating depression, and the effectiveness of megestrol acetate in addressing appetite and weight gain, prompted the Food and Drug Administration to authorize the use of progesterone for treating postpartum depression and cancer-related cachexia. Progesterone has also been found to alleviate neuropathic pain in animal studies. These off-label applications offer a promising option for patients with advanced cancer who often experience various mood disorders such as depression, persistent pain, social isolation, and physical complications like cachexia. These patients have shown low tolerance to opioids and mood-regulating medications. However, the potential risks and uncertainties associated with hormone therapy treatment modalities can be daunting for both patients and medical professionals. This review aims to offer a comprehensive understanding of the non-reproductive functions and mechanisms of female hormones in brain health.